Analisis kesalahan semantik hasil penerjemahan siswa SMA Al-Aziz IBS Bandung - Sawitri, Harani; Supriadi, Rinaldi; Tatang, Tatang (Universitas Lampung, 2023)
This study aims to reveal lexical semantic errors in the translation of Arabic story texts by students of SMA Al-Aziz Islamic Boarding School (IBS) Bandung. Analysis was carried out on translation errors found in the semantic aspect which are called semantic errors. Many semantic errors were found in the translation of Arabic into Indonesian by previous studies, but there were less of specifications. Semantic errors focus on the use of meaning that is not by the intent in the source language. This study used a qualitative approach with descriptive methods and error analysis techniques. The error description was based on James' theory (2013) which resulted in the discovery of 65 semantic errors which were divided into two categories, confusion of sense relation and collocation errors. This research is expected to be a reference for developing students' translation skills.Keywords: Error analysis, Semantic error, Translation